2020
DOI: 10.1016/j.cub.2019.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Inhibitory Circuits Integrate Visual and Gravitactic Behaviors

Abstract: Highlights d Negative gravitaxis in Ciona larvae is triggered by dimming illumination d Inhibitory input from the visual system suppresses gravitaxis until dimming d Output from the gravitaxis organ results in asymmetric motor inhibition d Reorientation behavior is evoked in downward-but not upward-facing larvae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 46 publications
(78 reference statements)
1
43
0
Order By: Relevance
“…To assess the behavior of larvae, we used a previously described gravitaxis assay [ 8 ]. In this assay, the behavior of larvae is recorded in a vertically mounted and covered 6-cm petri dish.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess the behavior of larvae, we used a previously described gravitaxis assay [ 8 ]. In this assay, the behavior of larvae is recorded in a vertically mounted and covered 6-cm petri dish.…”
Section: Resultsmentioning
confidence: 99%
“…For these assays presented here, which consisted of dimming a 505-nm light from 600 to 0 lux (while recording with constant 700-nm illumination), we recorded both the percentage of larvae responding to the dim, which was evident in recordings as swimming behavior initiated immediately following the light dim, as well as the direction of swim trajectories with respect to gravity for those larvae that did respond. All behavior assays were analyzed as described [ 8 ] and see the “ Methods ” section]. Briefly, trajectories were determined by assessing the starting and ending positions in the 20 s following dimming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a larval nervous system connectome has been revealed [ 28 ] and collections of single cell transcriptomics generated [ 29 , 30 , 31 , 32 , 33 ]. Emerging studies are now aiming to annotate each neuron identified in the connectome with the gene expression patterns, including neurotransmitter types, described from in situ hybridization/immunostaining analysis or single cell transcriptomics datasets, as well as to the cell lineage history and ultimately to neuronal function and larval behavior [ 29 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: The Ascidian Larval Cnsmentioning
confidence: 99%